Short-term effect of nd:yag laser capsulotomy on refraction, central macular thickness and retinal nerve fiber layer thickness - Cevher,Selim (2017)
Abstract Objective: The aim of this study is to examine the effect of Nd: YAG laser capsulotomy on refraction, central macular thickness (CMT) and retinal nerve fiber layer (RNFL) thickness. Methods: 42 eyes of 42 patients who treated with Nd:YAG laser capsulotomy were included in thisprospective study. Spherical equivalent (SE), cyclindrical power refraction, CMT and RNFL thickness were evaluated preoperatively and at postoperative first day, first week and postoperative first month. Results: Spherical equivalent values and central macular thickness values did not significantly change in the first month after treatment. Average and nasal retinal nerve fiber layer thickness values significantly increase and cyclindrical power refraction significantly decreased during the visits. Conclusion: Nd:YAG laser capsulotomy is confident and reliable treatment option of the posterior capsula opacification (PCO). After Nd: yag laser capsulotomy cyclindrical power refraction and RNFL thickness values significantly change.